Investigando o fenômeno magnetismo com alunos do 4º ano do Ensino Fundamental na perspectiva da alfabetização científica - Lopes, Elian Silva (2017)
This study is the result of a reflexion about Science Teaching by investigation, known as a methodology capable of contributing on the process of scientific literacy. The interest for the theme it's observed that physics knowledge isn't worked enough on initial years and there's also a lack of teaching methodologies that could contribute on the innovation of Science discipline. The problem can be seen through the question: the approch of magnetism phenomenom through Investigative teaching sequencies on initial years of fundamental school can lead to an appropriate learning of physics knowledge and contribute to Scientific literacy process? Intending on answering this question, a bibliographic research was made and an Investigative Teaching Sequency (ITS) was developed through the model proposed by Carvalho (2013)) entitled: Investigating the magnetism phenomenom on a 4th grade class of Fundamental School in Maceió's public schools. The study, developed in the qualitative method, had content analysis as the procedure of data interpretation, according to Bardin (2011). In that matter, we've used written productions (stories and cartoons) and recordings gathered on the study. The results have shown that students, when instigated to develop investigative experimental activities, similar to the ones realized by scientific academy, can improve conceptual contents, attitudinal and procedural, being capable of using them as a reading and compreehension instrument, giving meaning to the world they live in resulting in a scientific literacy.